Pediatric Appendicitis Score and Ultrasound in children with Acute Appendicitis: An Observational Study - Suyog Simkhada; Bijay Thapa; Anupama Thapa Basnet; Sijan Karki (Journal of Nepal Medical Association)
Introduction: Acute appendicitis is a common surgical emergency encountered in pediatric population. Differential diagnosis in this age group present with similar signs and symptoms. Clinical scoring system and Ultrasound imaging are helpful in diagnosing acute appendicitis and ruling out its differential diagnosis. This study was done to assess the findings of presence or absence of appendicitis in children based on the Pediatric Appendicitis Score (PAS) and ultrasound scan. Methods: An observational cross-section study was done from November 2023 to May 2024, in a tertiary level hospital, Kathmandu. All children between the ages of five and 14 years undergoing surgery for the provisional diagnosis of acute appendicitis were included in the study. The provisional diagnosis was based on a Pediatric appendicitis score and ultrasound. The diagnosis was confirmed by histopathology. Ethical approval was taken from Institutional Review Committee (Reference number: 811/2080/81). Results: A total of 50 children were included during the study period. A pediatric appendicitis score of more than seven, which is considered a high risk, was observed in 43 (86%) patients, and a score between four and six, which was considered an intermediate risk, was observed in 6 (12%) patients Similarly, 39 (78%) of the patient had appendix diameter more than six mm and 10 (20%) had less than six in ultrasound measurement. Conclusions: Both Pediatric Appendicitis Score and Ultrasonography can be used to diagnose acute appendicitis in children.